Synergistic Effect of Retinoic Acid Polymeric Micelles and Prodrug for the Pharmacodynamic Evaluation of Tumor Suppression - Zhu, Yan-Hua; Ye, Ning; Tang, Xin-Feng; Khan, Malik Ihsanullah; Liu, Hong-Liang; Shi, Ning; Hang, Li-Feng (Frontiers in Pharmacology, 2019)
All-trans retinoic acid (ATRA) is an effective agent that induces differentiation, inhibits cell proliferation, and acts as an anticancer agent. ATRA was successfully conjugated with Pluronic F127 via esterification to enhance its anticancer effects. Pluronic-ATRA showed high cytotoxicity and inhibitory concentrations (IC50) 50% lower than those of ATRA in various breast cancer cell lines (4T1:31.16–8.57 μg/mL; EMT6: 50.48–7.08 μg/mL; MDA-MB-231:37.58–8.99 μg/mL; BT474:25.27–9.09 μg/mL). In combination with chemotherapy, Pluronic-ATRA synergistically enhanced the cytotoxic effects of cisplatin (CDDP). Pluronic-ATRA combined with CDDP effectively suppressed breast tumor growth in vivo. The results of this study demonstrate the potential of Pluronic-ATRA as an anticancer agent that can be used in combination therapy against solid tumors.